Peningkatan Kreativitas Mahasiswa Dan Pemuda Dalam Mengembangkan Tanaman Sayuran Hidroponik Organik - Ilahude, Zulzain; Miolo, Sartin (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2019)
The objectives of this community service activity are 1) encouraging students and young farmers to master agricultural technology, 2) developing students' creativity in organic vegetable cultivation with hydroponic technology innovation, 3) utilizing organic waste such as animal manure, crop residues in the form of rice straw, sawdust  , husk charcoal, as a medium for organic fertilizer, 4) providing direct practice on how to make simple hydroponics, the importance of maintaining soil fertility for plants, and entrepreneurship.  Methods in the forming of direct application practice regarding making organic fertilizers, cultivating vegetables, and techniques for making simple hydroponics.  The locations of the activities are in the villages of Tunggulo, Tungulo Selatan, and Bongoime, Tilong Kabila District, Bone Bolango Regency, Gorontalo Province.  This activity was attended by 34 students' participants from the Department of Agrotechnology and other departments at State University of Gorontalo and collaborated with young farmers, held for 40 days from September 8 to October 10, 2020. The results of the activity showed that community service activities in partner villages were carried out running well and according to the planned program.  Students and young farmers have succeeded in developing hydroponic manufacturing techniques with vegetable commodities and organic growing media that use compost of manure and husk charcoal